A systematic review of the potential of a dynamic hydrogel as a substrate for sustainable agriculture - Sahmat, Siti Sahmsiah; Rafii, Mohd Y.; Oladosu, Yusuff; Jusoh, Mashitah; Hakiman, Mansor; Mohidin, Hasmah (MDPI, 2022)
Adopting environmentally friendly or green technology and incorporating new alternative substrates for a sustainable agricultural industry has garnered the attention of numerous researchers. Although super absorbent hydrogels have exhibited great potential, natural hydrogel-based absorbents have gained more interest due to their environmentally safe properties. The sources for the novel green polymer are easily obtained from agricultural wastes, such as polysaccharides, agarose, chitosan, and mucilage, with zero to minimal cost. The polymer also offers several attributes, including water usage and cost efficiencies, versatile application, and increasing plant growth. Furthermore, the polymer can act as a carrier agent and aid in improving the properties of planting mediums. The present review focuses on natural and chemical hydrogel-based polymers. It discusses their potential application in sustainable agriculture and the conservation of ecosystems by providing balanced protection for seeds, plants, and soil. Future perspectives based on previous investigations are also presented.